Circling Concepts : A Critical Archaeological Analysis of the Notion of Stone Circles as Sami Offering Sites - Spangen, Marte (Stockholms universitet, Institutionen för arkeologi och antikens kultur, 2016)
The thesis discusses a category of cultural heritage that has been labelled "Sami circular offering sites", aiming to establish some basic facts about their origin, distribution and use, as well as their cultural and socio-political context and influence. The stone enclosures in question have been interpreted as Sami offering sites since the mid-19th century, but a discourse analysis of the research history indicates that this may have been based on a scholarly hypothesis rather than ethnographic or archaeological evidence. Furthermore it is questioned if all the structures that are currently included in this category are in fact remains of the same cultural practice. This is investigated through surveys of 81 suggested circular offering sites in Norway, two excavations and analyses of the find material. The large stone enclosures in counties Finnmark and Troms that were first categorised in this way prove to have quite consistent builds and measurements and a find material mainly dating between the 13th and 17th centuries. These structures are here labelled type 1. In contrast, constructions that have later been added to the category, particularly in other areas, have other and less consistent characteristics and seem to include remains of a range of different activities. They are here divided into two generic types 2 and 3. The thesis further discusses alternative interpretations for the type 1 structures, concluding that their materiality, construction, location, topography and finds are consistent with archaeological, historical and ethnographic evidence for wolf traps. Their distribution indicates a regional Sami cultural practice related to inland winter habitation and travel routes, while also apparently coinciding with the Russian/Karelian taxation area in northern Norway in the Middle Ages. Thus the builds may have been inspired by the fur trade or other activities of the latter groups. It is uncertain when exactly the installations fell into disuse, as datings are calibrated to AD 1450-1650. The ...